Rigor by design, not chance : deeper thinking through actionable instruction and assessment - Hess, Karin (Karin K.) (ASCD, 2023)
"A practical and systematic approach to deepening student engagement, promoting a growth mindset, and building a classroom culture that truly supports thinking and learning"--